Feasibility and tolerability of multimodal peripheral electrophysiological techniques in a cohort of patients with spinal muscular atrophy - Leandra A.A. Ros; Boudewijn T.H.M. Sleutjes; Diederik J.L. Stikvoort García; H. Stephan Goedee; Fay-Lynn Asselman; Leonard H. van den Berg; W. Ludo van der Pol; Renske I. Wadman (Clinical Neurophysiology Practice, 2023)
Objective: Electrophysiological techniques are emerging as an aid in identifying prognostic or therapeutic biomarkers in patients with spinal muscular atrophy (SMA), but electrophysiological assessments may be burdensome for patients. We, therefore, assessed feasibility and tolerability of multimodal peripheral non-invasive electrophysiological techniques in a cohort of patients with SMA. Methods: We conducted a single center, longitudinal cohort study investigating the feasibility and tolerability of applying multimodal electrophysiological techniques to the median nerve unilaterally. Techniques consisted of the compound muscle action potential scan, motor nerve excitability tests, repetitive nerve stimulation and sensory nerve action potential. We assessed tolerability using the numeric rating scale (NRS), ranging from 0 (no pain) to 10 (worst possible pain), and defined the protocol to be tolerable if the NRS score ≤ 3. The protocol was considered feasible if it could be performed according to test and quality standards. Results: We included 71 patients with SMA types 1–4 (median 39 years; range 13–67) and 63 patients at follow-up. The protocol was feasible in 98% of patients and was well-tolerated in up to 90% of patients. Median NRS score was 2 (range 0–6 at baseline and range 0–4 at follow-up (p < 0.01)). None of the patients declined follow-up assessment. Conclusions: Multimodal, peripheral, non-invasive, electrophysiological techniques applied to the median nerve are feasible and well-tolerated in adolescents and adults with SMA types 1–4. Significance: Our study supports the use of non-invasive multimodal electrophysiological assessments in adolescents and adults with SMA types 1–4.